1972
DOI: 10.1111/j.1095-8649.1972.tb05669.x
|View full text |Cite
|
Sign up to set email alerts
|

The existence of natural hybrids between the European trout and the Atlantic salmon

Abstract: Natural hybrids between Atlantic salmon (Sulmo salar L.) and European trout (S. twtta L.) have been detected in a sample of 4431 fish which appeared to be Atlantic salmon. The methods of analysis for serum protein, serum esterase and serum lactic dehydrogenase are given. The possible Occurrence of hybrids having the appearance of European trout and the effect of introgression on salmon stocks are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

1973
1973
2007
2007

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 4 publications
1
28
0
Order By: Relevance
“…THE occurrence of wild F, hybrids between Atlantic saIanon (Sularao snhr) and brown trout (Sahno trufta) has been confirmed by gel electrophoresis in Great Britain, where the two species occur sympatrically (Payne et al 1972;Solomon and Child 1978). Other studies have confirmed the viability of artificially produced F, hybrids between these two species, as well as F3 hybrids ' and backcrc3sses (Catt 1950;Alm 1955: Piggins 1565, 1966.…”
mentioning
confidence: 86%
“…THE occurrence of wild F, hybrids between Atlantic saIanon (Sularao snhr) and brown trout (Sahno trufta) has been confirmed by gel electrophoresis in Great Britain, where the two species occur sympatrically (Payne et al 1972;Solomon and Child 1978). Other studies have confirmed the viability of artificially produced F, hybrids between these two species, as well as F3 hybrids ' and backcrc3sses (Catt 1950;Alm 1955: Piggins 1565, 1966.…”
mentioning
confidence: 86%
“…Although esterase isoenzyme patterns are usually species-specific, especially in fish (Payne et al, 1972;Reinitz, 1977;Solomon and Child, 1978;Ferguson, 1980), our investigation showed no cytotype-specific fixed allele in the three esterase-D loci for the three piranha karyotypic structures examined. Generally, species are typically fixed for different alleles on the same locus, while co-specific populations typically differ in regard to the same allele frequencies (Smith et al, 1981).…”
mentioning
confidence: 46%
“…Many enzymes, such as esterases, show pronounced differentiation in isoenzymatic patterns in many organisms, including plants (Anti, 2000), phytonematoids (Alonso and Alfenas, 1998), mollusks (Richardson et al, 1982) and fish (Payne et al, 1972;Reinitz, 1977;Solomon and Child, 1978;Ferguson, 1980). Although Serrasalmus is one of the most widespread and specious South American piranha genera (Machado Allison and Fink, 1995) only a few allozyme genetic studies have been carried out on this piscine group since the study of Serrasalmus spilopleura lactate dehydrogenase (LDH), malate dehydrogenase (MDH) and glucose phosphate isomerase (GPI) isoenzyme patterns by Cestari (1996) on fish from the Paraná and Paraguai river basins.…”
mentioning
confidence: 99%
“…spectabile and E. caeruleum would be expected to be heterozygous at those loci at which different alleles are fixed or in high frequencies in the respective parental populations (Payne et al, 1972). Table VI shows that none of the presumed hybrid individuals were heterozygous at the TO, EST2, LDH, and MDHloci.…”
Section: Discussionmentioning
confidence: 98%